Financial Management of Surface Treatment Company through Tax Planning - Ragil Alfiyani Mabruroh; Mukti Prasaja; Aan Nurrohman; Koerniawan Dwi Wibawa (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
This research aims to determine a value-added tax plan for tax efficiency and to increase the cash flow of PT. Abimanyu Sekar Nusantara. The method of deferring input tax crediting was used in this study. So that the input tax issued is smaller, making cash flow appropriate that the company expects. The problems that occurred at PT. Abhimanyu Sekar Nusantara is not yet implementing tax planning so that taxes The input issued is still quite large. The types of data used are Qualitative. Primary and secondary data are references to the information used. The method of data collection is through documentation as well as interviews directly to the Supervisor of the Finance and Accounting section of PT. Abimanyu Sekar Nusantara. The data analysis technique uses qualitative, namely by collect data, further simplify the data that has been collected, After that, the data is processed to produce conclusions in order to be efficient input tax to increase the company's cash flow. Research results indicates that the delay in the crediting of input tax in the planning Taxes are not efficient enough. The author can only offset the payment of taxes every month. However, the results of this delay may affect related An increase in cash flow even though it is only 11%. Keywords: Tax Planning; Value Added Tax; Crediting Delay; Input Tax; Cash Flow